2019
DOI: 10.1063/1.5110363
|View full text |Cite
|
Sign up to set email alerts
|

Oxide shell layer influences on size-dependent tensile and compressive mechanical properties of iron nanowires: A ReaxFF molecular dynamics study

Abstract: The systematic understanding of an overall deformation mechanism of metallic iron (Fe) nanowires (NWs) with the pre-existing oxide shell layer (Fe/Fe x O y ) under various mechanical loading conditions is of critical importance for their various applications. Herein, we perform molecular dynamics simulations using ReaxFF reactive interatomic potential to systematically investigate the effect of the pre-existing oxide shell layer on the underlying intrinsic mechanical deformation mechanism and related mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…34 ReaxFF has been successfully used for various systems, such as metallic Al, Ni, and Fe NWs to obtain insight into the oxidation of reactive complex materials and its responsible impact on degradation of mechanical deformation performance and predict related physical and chemical properties. 17,[26][27][28][29][30][31][32][33] Furthermore, these previous studies revealed that oxidized metallic NWs exhibit to have unique mechanical properties, which depends on several factors, such as the oxide shell layer thickness, the local structure of the oxide shell layer with the combined effect of the externally applied mechanical loads, determining the overall stress-strain behaviors in the NWs and the deformation mechanism and properties.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 ReaxFF has been successfully used for various systems, such as metallic Al, Ni, and Fe NWs to obtain insight into the oxidation of reactive complex materials and its responsible impact on degradation of mechanical deformation performance and predict related physical and chemical properties. 17,[26][27][28][29][30][31][32][33] Furthermore, these previous studies revealed that oxidized metallic NWs exhibit to have unique mechanical properties, which depends on several factors, such as the oxide shell layer thickness, the local structure of the oxide shell layer with the combined effect of the externally applied mechanical loads, determining the overall stress-strain behaviors in the NWs and the deformation mechanism and properties.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…The generated overall average stress vs strain is calculated from each atom using the virial theorem during the deformation process, which is corrected by the true volume of the NWs in order to obtain the engineering stress-strain curves in the [001]-oriented direction for each NW, as we used in previous MD simulations. 23,[26][27][28][29][30][31][32][33] The uniaxial tensile strain is applied until reaching at ∼28% elongation. Equations of motion are integrated with the velocity of the Verlet algorithm using a time step of 0.25 fs in all simulations.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Another aspect in connection with mineral materials that serve as feedstock for sustainable metal production processes is their porosity as well as their mechanical properties at higher temperatures. ,,, In the latter context, in particular compressive strength, fracture toughness, and abrasion response matter. The reason for placing attention on these specific features is that the ores as well as their refined and sintered pellet agglomerates experience high static and dynamic loads in shaft and fluidized bed furnaces, all at high temperatures between 600 and 950 °C. During these loading scenarios they can undergo fracture, softening and abrasion processes which can lead to the accumulation of fine oxide dust between the ore pellets.…”
Section: Feedstock For Sustainable Metal Production: Minerals Metals ...mentioning
confidence: 99%